Evaluation of neuroprotective effects of tualang honey on paraquat-induced oxidative stress & dopaminergic neuron damage in the rat brain - Sulaiman, Siti Amrah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Background: Paraquat is a dopaminergic neurotoxin and exerts its toxic effect via oxidative stress-mediated cellular injuries. The protective effects of Tualang honey on paraquat-induced toxicity in the midbrain and lungs of rats were investigated. Methods: Male Sprague Dawley rats were randomly divided into five groups; : control (N), honey (TH), paraquat (PQ), paraquat + honey (PQ+ TH) and paraquat + ubiquinol (PQ+QH). The rats were orally treated with distilled water (groups N & PQ, 2 mLkg/day), Tualang honey (groups TH & PQ+TH, 1.0 g/kg/day) or ubiquinol (group PQ+QH, 0.2 g/kg/day) throughout the experimental period. Two weeks after the respective treatments, rats were administered intraperitoneal injections of saline (Groups N & TH; 1 mLkg/week) or paraquat (10 mg/kg/week; groups PQ, PQ + TH & PQ + QH) once a week for four consecutive weeks. Animals were sacrificed a week after the last injection of saline/paraquat. The midbrain and lungs were collected for biochemical (n=8) and immunohistochemical (n=7) assessments. Results: The present study showed that exposures to paraquat induced oxidative stress in both the midbrain and lung regions. In the midbrain region, the activity of glutathione peroxidase (GPx) and the amount of tyrosine-hydroxylase (TyrH)-immunopositive neurons were significantly reduced in animals from group PQ. However, treatment with Tualang honey ameliorated these toxic effects. The lungs of group PQ showed a statistically significant reduction in superoxide dismutase (SOD), glutathione-S-transferase (GST) and total glutathione (GSH) activities. Treatment with honey (group PO-t TH) significantly increased SOD activity in the lung (p < 0.05) and ameliorated the loss in GST activity and the total GSH concentration compared to group PQ. The beneficial effects of Tualang honey were comparable to ubiquinol, which was the control drug used in this study. Conclusions: These findings suggest that Tualang honey may protect against paraquat-induced toxicity in rats.